PENGARUH SOSIALISASI ORANG TUA TERHADAP PERILAKU KONSUMTIF SISWA - Mecy Agusmin; Arwin Arianto; Venny Chairani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2018)
This study aims to examine the effect of socialization parents against consumtive behavior of students class X in Senior High School 4 Pagaralam. This research method is associative research. The samples used in this research are 64 students of X class of IPS Department in SMA Negeri 4 Pagaralam. Primary data collection techniques using questionnaires. Data analysis technique used is simple regression analysis. The results of this study there is a significant effect of parental socialization on consumptive behavior where the effect is positive. The findings of this study that the parents' socialization influence on student consumptive behavior is 39.3% while the rest is influenced by other factors not examined in this study